Web App for Visual Project Management - S, Gayathiri; E, Saravanan; M, Vishvanth (Journal of Neonatal Surgery, 2025)
Modern teamwork relies heavily on effective collaboration, but inefficiencies like improper task allocation, miscommunication, and inadequate progress tracking frequently hinder productivity. To address these challenges, this project introduces a Web-Based Task Management System aimed at streamlining group work processes by providing a centralized platform where teams can organize, prioritize, and track tasks efficiently, fostering improved coordination and communication. With features such as task creation, assignment, priority setting, real-time progress monitoring, in- app messaging, and notifications, the platform ensures that all team members stay aligned with project goals while enhancing collaboration and reducing delays. Unlike existing fragmented systems that separate task tracking and communication, the proposed solution integrates these functions to deliver a seamless experience. Additional features like role-based access control, automated reminders, file sharing, and performance analytics further support accountability and productivity. The system is adaptable to a variety of industries, including event planning, corporate management, education, and scalability. It was designed with cross-device accessibility, security, and scalability in mind. Its implementation demonstrates significant improvements in transparency, coordination, and overall efficiency, empowering teams to achieve their objectives more effectively and making group work more productive, transparent, and goal-oriented